2021
DOI: 10.1111/cag.12677
|View full text |Cite
|
Sign up to set email alerts
|

Supporting food security for Indigenous families through the restoration of Indigenous foodways

Abstract: Indigenous families are overrepresented among those within Canada who experience food insecurity. Studies have largely focused on northern populations, with less attention paid to southern and urban communities, including the social, cultural, and geographic processes that challenge food security. In this study, we present findings from a decade‐long community‐based study with the Southwest Ontario Aboriginal Health Access Centre (London, Ontario) to examine family perspectives related to the social determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The more recent conceptualisation of food security to include agency and sustainability as key dimensions highlights the possibility of moving towards a food sovereignty approach. Food sovereignty implies a broader vision of food security, moving away from an individualised focus to one that disrupts and reimagines food systems so they are democratically managed and geographically specific [ 72 , 73 ]. Food sovereignty has been conceptualised within First Nations contexts, as having seven pillars: (1) focuses on food for people; (2) builds knowledge and skills; (3) works with nature; (4) values food providers; (5) localizes food systems; (6) puts control locally; and (7) allows that food is sacred [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The more recent conceptualisation of food security to include agency and sustainability as key dimensions highlights the possibility of moving towards a food sovereignty approach. Food sovereignty implies a broader vision of food security, moving away from an individualised focus to one that disrupts and reimagines food systems so they are democratically managed and geographically specific [ 72 , 73 ]. Food sovereignty has been conceptualised within First Nations contexts, as having seven pillars: (1) focuses on food for people; (2) builds knowledge and skills; (3) works with nature; (4) values food providers; (5) localizes food systems; (6) puts control locally; and (7) allows that food is sacred [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…A primary driver is the high price and decreased access to healthier food options and safe drinking water [18]. In Canada, a review of obesity among First Nations communities observed that fluctuating food prices by season, lack of access to healthy food options, and ease of access to convenience stores are factors in the increased levels of obesity [12,19]. A past review examining food access for Indigenous people globally highlighted that, for rural and remote indigenous peoples in Australia, Canada, Greenland, Guam, and the United States, often stores do not carry fresh items such as produce, dairy, and meat [16].…”
Section: Choicesmentioning
confidence: 99%
“…Finally, Richmond and colleagues share the results of a community‐engaged study that explored the social, cultural, and geographic processes that challenge food security among First Nation mothers living on‐reserve and in urban contexts in southwestern Ontario (Richmond et al 2021). Results from interviews and focus groups with First Nation mothers indicate culturally and geographically relevant insights about the nature of food security.…”
mentioning
confidence: 99%